2016
DOI: 10.1080/00016489.2016.1191671
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma ex pleomorphic adenoma of the parotid gland: a multi-institutional retrospective analysis in the Northern Japan Head and Neck Cancer Society

Abstract: The 3-year overall and progression-free survival rate of all patients was 79.9% and 76.8%, respectively. Both the 3-year overall and progression-free survival rates were 87.5% for patients with non-invasive SDC or adenocarcinoma NOS. The 3-year overall and progression-free survival rates for patients with invasive SDC or adenocarcinoma NOS were 60.4% and 30.5%, respectively. The progression-free survival rates for patients with invasive SDC or adenocarcinoma NOS was significantly poor (p < 0.05).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…Not surprisingly, a previous research effort addressed that the mean age of CXPA is 61 years, 5 and another study with smaller number of patients showed that the median age of CXPA is 60 years. 11 Our study showed that the average was slightly lower (55.1 years old) than these previous studies. When compared to pleomorphic adenoma, the mean age of diagnosis was significantly different by approximately 13 years ( Figure 1A, 55.1 vs 42.3, respectively, P ¼ .001).…”
Section: Comparison With Other Studiescontrasting
confidence: 68%
“…Not surprisingly, a previous research effort addressed that the mean age of CXPA is 61 years, 5 and another study with smaller number of patients showed that the median age of CXPA is 60 years. 11 Our study showed that the average was slightly lower (55.1 years old) than these previous studies. When compared to pleomorphic adenoma, the mean age of diagnosis was significantly different by approximately 13 years ( Figure 1A, 55.1 vs 42.3, respectively, P ¼ .001).…”
Section: Comparison With Other Studiescontrasting
confidence: 68%
“…The authors showed that CA-xPA is a more aggressive cancer compared to primary parotid cancer. The extent of CAxPA occurred significant in prognosis.. Suzuki et al demonstrated 3-year disease free survival for non-invasive CAxPA at a level of 79.9% and 76%, respectively for histopathological types of ductal carcinoma and adenocarcinoma [24]. In the same work, the percentage of recurrance--free survival for invasive forms of both CAxPA types was 60% and 30%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Historical reports list 5-year survivals ranging from 30% to 70% 4 . The tumour often arises from the background of a recurrent pleomorphic adenoma and can be composed of various histologic subtypes, including high-grade salivary duct carcinoma, adenocarcinoma not otherwise specified, myoepithelial carcinoma, and sarcomatoid carcinoma, among others 2 .…”
Section: Discussionmentioning
confidence: 99%